Assessment of Health Supply Chain Risks in Uganda: The Case of Uganda Health Supply Chain Project - Wasswa, John Hans; Namulindwa, Angella (V, 2020)
This study aimed at assessing risks affecting Health supply chains in Uganda using a case of Uganda Health Supply Chain project. The theoretical framework onto which this study was anchored was the normative decision theory of risk management. A cross sectional study design was adopted employing the quantitative research approach. A sample population of 196 was used and primary data was collected using self-administered questionnaires and analyzed using STATA statistical program. Descriptive data was presented in form of graphs and frequency distribution tables. It was later analyzed and interpreted using percentages, frequencies, means, and standard deviations. The study results revealed that the greatest health supply chain risks faced by health supply chain programs in Uganda were; Financial-related risks such as cost overruns; and End user-related risks such as poor quality health commodities, poor feedback mechanisms and loss of patient lives. Other major risks discovered by the study included demand and supply-relate drisks resulting from supplier unpredictability such as stock outs; Procurement-related risks such as long lead-times and inadequate technical input; and distribution and Storage-related risks. Environmental-related risks such as accidents, bad weather and political instability were the least faced risks. The study concluded that health supply chains in Uganda are troubled by a multitude of risks, and therefore the study recommended that,after a clear understanding of risks affecting health supply chains has been uncovered, carefully-tailored standard risk management processes can be established within health supply chain projects to improve the functionality of Uganda’s health supply chain management systems.
Keywords: Health supply chain risks; Health supply chain projects; Risk management; Health supply chain management system